Hukuman (Punishment) dalam Perspektif Pendidikan di Pesantren - Ma’arif, Muhammad Anas (Taallum: Jurnal Pendidikan Islam, 2017)
The phenomenon of punishment that implanted in pesantren is one of the educational method that often used by educators to overcome the students who behave less well with the reason to improve the behavior of learners. Even such punishment leads to the violence. The importance of discussion its punishment in pesantren is because it is considered less relevant to education today. This study aims to explain the reasons why the teachers in boarding schools apply penalties for violators of the boarding school and is there any impact from it. The researcher conducted an indepth interview of punishment phenomenon in pesantren to find the data as much as possible for complete result. So the result of this research is the punishment given to students must appropriate to the procedure. So students can feel positive impact caused by the punishment.